New Afrotropical species of the genus Coridiellus J.A. Lis, 1990 with a key to its species (Hemiptera: Heteroptera: Dinidoridae) - Kocorek, Anna (Zootaxa, 2020)
Coridiellus pseudocyclopeltus, a new species of the dinidorid subfamily Dinidorinae, is described from Zaire and is compared with Coridiellus cyclopeltus (Distant, 1890). It is the seventh species of this genus known from Afrotropical Region. A key to all the species of the genus Coridiellus is also provided. Male parameres are used for identification and their photographs are given for the first time for all species of the genus.